A numerical assessment of the heterogeneous effects of innovative shroud profiles for horizontal axis wind turbine - Hossam Hamid; Rafea Mohamed Abd El Maksoud (Heliyon)
Wind turbine control is critical in power generation from wind, thus assuring great efficiency and cost-effectiveness. This has been a subject of intense research, and its advancements are critical to developing even better and efficient wind turbines. This research looks at several passive flow control mechanisms for horizontal wind turbines. When looking for effective and affordable systems, the diffuser-augmented turbine appears to have a potential role in boosting power output and lowering system costs, especially at low speeds. The primary goal is identifying the optimal shroud design that maximizes turbine performance. A numerical investigation of various shrouds was conducted to identify the relationship between power augmentation and wind speed for wind turbines. The turbulence model SST k-ω was selected during the computational studies. The shroud length, and diffuser opening angle; in addition to amplitude and wavelength for the shroud with bio-inspired tubercles are the main parameters in the present study. The outcome was validated with previous studies. Based on the numerical simulations, the multi-element airfoil-shaped shroud of the E423 airfoil profile was chosen. The highest increase in wind speed reached more than 2 times the free-stream wind speed, which indicates that the turbine power production could increase up to 8 times at the same free-stream wind speed.